Vitamin D non-sufficiency is prevalent in children with chronic liver disease in a tropical country - Way Seah Lee; Muhammad Yazid Jalaludin; Shin Yee Wong; Sik Yong Ong; Hee Wei Foo; Ruey Terng Ng (Elsevier, 2019)
Background: To determine vitamin D status in children with chronic liver disease (CLD) in a tropical country. Methods: Cross-sectional study in Malaysian children with CLD. Factors affecting serum vitamin D level (definition: deficient < 30 nmol/L; insufficient 30-50 nmol/L; sufficient ≥ 50 nmol/L) was analyzed. Results: Of the 59 children studied (males 32, 54%; median age 6.8 ± 5.3 years), the three most common causes were biliary atresia (n = 25), autoimmune hepatitis (n = 16) and sclerosing cholangitis (n = 6). The overall mean daily vitamin D intake was 715 ± 562 units/day. Thirteen (22%) patients had at least one clinical signs of rickets. Seventeen (29%) had serum bilirubin level ≥ 34 μmol/L. Eight (14%) children were deficient in vitamin D, eight (14%) were vitamin D-insufficient and 43 (73%) were sufficient. As compared with children with serum bilirubin <34 μmol/L, those with serum bilirubin ≥34 μmol/L were more likely to have rickets (24% vs. 65%; P < 0.002) and a lower serum vitamin D level (86.0 ± 54.9 nmol/L vs. 65.4 ± 48.2 nmol/L; P = 0.05) despite being given a significantly higher vitamin D dose (608 ± 571 vs. 970 ± 543 units/day; P = 0.008). The proportion of children with either deficient or insufficient vitamin D status was significantly higher in children with bilirubin level ≥34 μmol/L than in children <34 μmol/L (47% vs. 19%; P = 0.028). Conclusion: Vitamin D deficiency and insufficiency is common in children with CLD in a tropical country. Regular monitoring of vitamin D status and screening for metabolic bone disease in all children with CLD is recommended. Higher dose of oral supplement or parenteral route should be considered, especially in those with bilirubin ≥34 μmol/L. Key Words: chronic liver disease, vitamin D deficiency, tropical country